[International Exhibition, 1862] : [collection of illustrations] - National Art Library (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 2007)
Electronic reproduction of illustrated plates and extracts from newspapers; from a collection in the National Art Library, Victoria and Albert Museum